A diagnosis of the economic situation of the lobster fishing industry in Ceará State, Brazil - Fonteles-Filho, Antonio Adauto; Guimarães, Maria Socorro Sobral (Arquivos de Ciências do Mar, 2017)
The lobster fishery, as an extractive, industrial and commercial activity, spans the primary, secondary and tertiary sectors of the Economy. In the primary sector it sustains running costs through construction of boats (U$$ 13.5 million) and fishing gears (US$ 2.5 million), and wage payments (US$ 2.3 million); in the secondary sector, it sustains costs with labor, equipments and plant installations; in the tertiary sector, it earns revenues from product sales used for offsetting the expenses made in the other two sectors. On a socioeconomic steady state, the lobster fishery participates with revenues and costs alike amounting to US$ 52.0 million, its fishing fleet is worth US$ 13.7 million and it spends US$ 2.3 million with salaries for fishermen and US$ 2.5 million for the making of fishing gears, generating 10,823 direct jobs in the primary sector, 1,012 in the secondary sector and 20 in the tertiary sector. The low rate of industrial utilization and rising costs contributed to sharp changes in the activitry strategy and production financing. The Production subsector aggregates most of the capital of the fisheries sector, and herein the monetary strategy favors the profit (US$ 39.5 million) but not job opportunities which remain as low as 4,120, the bioeconomic strategy generates an equilibrium between revenue US$ 64.0 million and job opportunities as 6,606 posts, and the socioeconomic strategy favor job opportunities (10,654) but not revenue (US$ 52.0 million). The socioeconomic is the strategy adopted at the present time for whose maintenance a reduction in the tax over trading from 17% to 1.7% meant only US$ 0.9 million earned by the government as duties collection. An ideal management system should generate a revenue of US$ 64.0 million, a profit of US$ 34.9 million, 6,606 jobs in the primary sector, US$ 3.00 per trap-day, a benefit/cost ratio of 2.20 and 54.5% of marginal profit. Despite the drawbacks, one may conclude that the lobster fishery is still a very important economic activity, being accountable for the earning of foreign currencies through exportation and a large share of the job opportunities in Ceará State.